The models of subordination in the mechanized section on M-80A infantry fighting vehicle - Žnidaršič Vinko; Veličković Branko; Mutavdžić Dobrivoje (Војно дело, 2021)
The organization of command in the mechanized section on M80A infantry fighting vehicle is defined by the regulations and textbooks of mechanized units. The problem that is not covered in the regulations is the organization of subordination of soldiers of the mounted crew when performing tasks outside the vehicle. The regulations stipulate in principle that command is executed by single seniority and subordination, but that the mechanized section commanders organize their crews in the way they think is appropriate, in accordance with a certain mission and tasks. The decision-making on transfering commanding competencies and organization of subordinates in the chain of subordination within the mechanized section is a dilemma even for experienced commanders of mechanized units because this is defined by general principles of performing activities, whereby it is not known where the riflemen, sniper and machine gunners should be when they are outside the fighting vehicle. During preparation and execution of activities, the mechanized section commander should adapt the model of subordination in relation to task, space, time and other factors that occur in combat operations. Thus, it can happen that the commander or deputy commander divides the mounted part of the mechanized section into several smaller units (groups, teams) in order to perform some task. The research performed by the analysis of content in regulations and textbooks, observing the way of work during the performance of activities, anticipating possible situations and discovering examples of good practice of the mechanized section commanders, the models presented in this paper have been formed. After studying literature and questioning professional military personnel, the results of the research are the models of subordination in the mechanized section when the mounted part of the section is outside the vehicle. The analyzed models are divided into groups of models, where the dismounted part of the section is divided into: 1) basic model, 2) two groups and 3) three groups.